Development and Validation of UV Spectrophotometric methods for simultaneous estimation of Lobeglitazone Sulfate and Glimepiride in combined dosage form - Patel, Dhara; Dobariya, Jeel; Pradhan, Prasanna; Patel, Grishma; Meshram, Dhananjay (Drug Analytical Research, 2026)
Two UV spectrophotometric methods have been developed for accurately analyzing Lobeglitazone Sulfate and Glimepiride in combined dosage form, used in the treatment of type 2 diabetes mellitus. Method I, known as the simultaneous equation method (Vierodt’s Method), relies on measuring the absorption at 250 nm for Lobeglitazone Sulfate and 227 nm for Glimepiride, their respective λmax values. Method II involves the second-order derivative method, where the absorbance of Lobeglitazone Sulfate is measured at 297 nm (zero-crossing point of Glimepiride), and that of Glimepiride is measured at 259 nm (zero-crossing point of Lobeglitazone Sulfate). Both methods exhibit linearity within specified concentration ranges: 3-13 μg/mL for Lobeglitazone Sulfate and 6-26 μg/mL for Glimepiride, using methanol as the solvent. The accuracy of these methods was confirmed through recovery studies, yielding results within the range of 98-102% for both drugs. Precision was evaluated through repeatability and intermediate precision studies, demonstrating % RSD values below 2%, indicating high precision. A comparison between the two methods using the F-test showed no significant difference. Statistical validation according to ICH Q2 R1 guideline confirmed the reliability of the results obtained from both methods.